(untitled) (Journal of Universal Science Research, 2025)
The purpose of this study is to evaluate the effectiveness, safety, and clinical outcomes of extracorporeal shock wave lithotripsy (ESWL) in the treatment of renal and upper ureteric calculi. Kidney stones are a common urological condition, and non-invasive management options have become increasingly important. ESWL uses focused acoustic pulses to fragment stones, allowing natural passage through the urinary tract. This work aims to assess the stone clearance rate, number of sessions required, and incidence of complications. Additionally, it evaluates factors influencing treatment success such as stone size, location, and composition. The findings are intended to guide optimal patient selection for ESWL and to compare its efficiency to other modalities such as ureteroscopy and percutaneous nephrolithotomy